Coronary flow velocity reserve predicts adverse outcome in patients with angina and no obstructive coronary artery disease. (25th November 2020) - Schroder, J; Michelsen, M.M; Mygind, N.D; Frestad, D; Suhrs, H.E; Bove, K.B; Aziz, A; Hansen, H.S; Hansen, P.R; Gustafsson, I; Kastrup, J; Prescott, E
Abstract: Background: Many patients with angina do not have obstructive coronary artery disease (CAD) when evaluated with coronary angiography. It is unknown whether echocardiographic coronary flow velocity reserve (CFVR) predicts an adverse outcome in these subjects. Previous CFVR studies have included heterogeneous patient subtypes both with and without CAD. Purpose: To assess whether reduced CFVR predicts adverse outcome in women with angina and no CAD. Methods: We evaluated 1853 women with angina and a coronary angiogram without stenosis. Exclusion criteria were previous myocardial infarction, coronary revascularisation, heart failure or valvular disease. Coronary microvascular function was assessed by echocardiographic CFVR. All patients were followed up for major adverse cardiovascular events. Results: CFVR was obtained in 1681 patients (91%), median CFVR was 2.33 (IQR 2.00–2.74). During a median follow-up of 4.48 years, 96 adverse events occurred (acute myocardial infarction: 25; heart failure: 21; revascularisation: 8; stroke: 32; cardiovascular death: 10). In univariate Cox regression, CFVR (hazard ratio [HR] 2.04 [95% CI 1.39–2.94] per unit decrease in CFVR; p<0.001), hypertension (HR 2.29 [95% CI 1.46–3.59]; p<0.001) and diabetes (HR 2.13 [95% CI 1.31–3.45]; p=0.002) were associated with adverse outcome. These associations remained in age-adjusted multivariable regression. Exploratory analyses identified CFVR=2.24 as the optimal discriminating threshold. Stratification according to reduced CFVR and hypertension identified subgroups with better, intermediate and worse outcome (Figure 1). Outcome analyses excluding stroke yielded similar results. Conclusion: Impaired CFVR predicts adverse outcome in women with angina and no CAD. Integrating CFVR and hypertension identifies high-risk patients. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The Danish Heart Foundation